Considering District and School Factors and Their Relationship to ACT Performance in North Carolina: An Examination of the ACT Pilot Results. (4th March 2014) - Kaniuka, Theodore S.
Abstract : Since 2001 several states have adopted the requirement that high school students either take the SAT or ACT to assess high school programs or assist students in accessing post-secondary-educational opportunities. In 2012 the state of North Carolina adopted a new accountability program that included the ACT as a measure of college readiness. Previous research on the relationship between school districts and school level performance found that district size had a role in school achievement. This study looked at how district factors influenced the ACT performance of students across North Carolina in an effort to better understand if there were district factors other than size that may be influencing student performance and how high school reforms, given the influence of district factors is meeting the goal of increasing student college readiness. The results of this study are as follows. (1) District factors are related to school level performance, where student race and parental education levels were found to be significant predictors of achievement, (2) the traditional school level factors of race and student socioeconomic status did significantly predict ACT scores, and (3) as a high school reform model, students attending early college high schools did score higher on the ACT as compared to traditional high schools.